Eogenetic diagenesis of Chinle sandstones, Petrified Forest National Park (Arizona, USA): A record of Late Triassic climate change. Issue 4 (26th December 2017) - Jin, Cong; Dworkin, Steve; Atchley, Stacy; Nordt, Lee
Abstract: Fluvially derived tuffaceous Chinle sandstones from Petrified Forest National Park provide a well‐preserved Late Triassic archive of climate information. Petrographic analysis of 38 Chinle sandstones provides new insight into the depositional history and evolution of palaeoclimate during Chinle deposition. This study focuses on the relationship between climate and meteoric diagenesis as a guide for constraining climate change in western equatorial Pangea during the Late Triassic. Petrographic analysis of Chinle sandstones reveals their wide range of textural attributes, as well as pedogenic and shallow burial diagenetic features that occurred during the Late Triassic. These diverse petrological characteristics are indicative of the evolving Late Triassic climate, when placed into a well‐constrained stratigraphic and geochronological framework. The stratigraphic succession is characterized by variations in the abundance of framework grains, detrital matrix, weathering intensity of feldspar and volcanic rock fragments, and the mineralogy of clay cements. Climate records from Chinle palaeosol geochemistry indicate a progression from wet to dry conditions. This trend is also reflected in the meteoric diagenetic features of Chinle sandstones. During deposition of the lower Chinle, elevated rainfall promoted the weathering of labile volcanic detritus to kaolinite, whereas feldspars (especially plagioclase) were partially or completely dissolved. In the upper Chinle, a trend towards drier conditions favoured the formation of smectite and less feldspar dissolution resulting in a higher abundance of well‐preserved plagioclase grains. Shallow burial meteoric weathering reactions in Chinle sandstones reflect the evolving climate during the Late Triassic.